AKAL DALAM PERSPEKTIF FILSUF DAN SUFI - Ali Sodikin (MIYAH : Jurnal Studi Islam, 2020)
Abstract: Intellect (Al-'aql) in Arabic means bond, is the key to understanding Islam. Intellect is a place / container that accommodates faith, shari'ah and morals. Meanwhile the heart is the realm of essence. Human reason that fulfills the requirements to make every effort to understand the legal principles contained in the Al-Quran and Al-Sunnah then formulates and applies them in life or formulates legal principles if they are not found in the Al-Quran and Al-Sunnah. According to Muslim philosophers, a mind which has reached the highest level - intellect acquiring (intellect mustafad) - can know happiness and seek to obtain it. Such intellect will make his soul eternal in happiness (heaven). However, if the mind that has known happiness turns away, it means that it is not trying to obtain it. Such a soul will be eternal in misery (hell). Meanwhile, according to the Sufi, in the concept of insan kamil, humans are not the most perfect in their thinking and are able to understand everything in the world exactly as in reality, because they doubt the validity of understanding the mind itself, which is considered something very limited.Keywords: Intellect, Philosophy and Sufi